2016
DOI: 10.1136/bjophthalmol-2016-308900
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: applicability and compliance of guidelines in Hong Kong

Abstract: Current ROP screening using the UK guidelines (2008) is applicable, effective and safe to our predominantly Asian population in Hong Kong, with a low rate of delayed screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…Previous studies showed that many hospitals in Hong Kong follow the UK screening criteria for ROP screening [7][8][9]26,27 ; consistent with our findings, the reported incidences of ROP and type 1 ROP in Hong Kong were 16% to 28% 7-9 and 3.4% to 3.8%, [7][8][9] respectively. In the present study, type 1 ROP mainly developed in extremely preterm infants with a median GA of 26 weeks and 0.5 days (IQR=2 weeks & 2.5 days), suggesting that low GA was an important predictor of type 1 ROP in our population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies showed that many hospitals in Hong Kong follow the UK screening criteria for ROP screening [7][8][9]26,27 ; consistent with our findings, the reported incidences of ROP and type 1 ROP in Hong Kong were 16% to 28% 7-9 and 3.4% to 3.8%, [7][8][9] respectively. In the present study, type 1 ROP mainly developed in extremely preterm infants with a median GA of 26 weeks and 0.5 days (IQR=2 weeks & 2.5 days), suggesting that low GA was an important predictor of type 1 ROP in our population.…”
Section: Discussionsupporting
confidence: 91%
“…5,6 In Hong Kong, many hospitals use the UK screening criteria to guide ROP detection. [7][8][9] Although the UK screening criteria are appropriate for ROP detection in many countries, [10][11][12] they are not universally appropriate. [13][14][15][16][17][18] In India 14,15,19 and China, 17,18 some infants with GA and BW above the UK screening thresholds also developed severe ROP requiring treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In our clinic, we found the incidence of ROP to be 16.2% during a three-year follow-up, in infants with a birth weight of less than 32 weeks and/or birth weight of less than 1500 g, and infants with a birth weight of over 32 weeks and/or birth weight of over 1500 g, who required cardiorespiratory support and determined to be at risk of ROP by the clinician. Our ROP frequency was found to be lower when compared to the results reported from countries that applied similar screening protocols in the literature [6,[10][11][12] .…”
Section: Discussioncontrasting
confidence: 56%
“…Recent reports suggest between 9–40% of screened infants will develop ROP, and an even smaller number will require treatment. 78,135,136,230,239,255 ROP examinations can cause significant morbidity in neonates, including decreased oxygen saturation levels, increased heart rate, and increased apnea events. Also, unnecessary examinations may increase the medical costs for ROP screening.…”
Section: Retinopathy Of Prematuritymentioning
confidence: 99%